2022
DOI: 10.3390/biology11091329
|View full text |Cite
|
Sign up to set email alerts
|

Trophism and Homeostasis of Liver Sinusoidal Endothelial Graft Cells during Preservation, with and without Hypothermic Oxygenated Perfusion

Abstract: The aim of the present study was to evaluate the homeostasis and trophism of liver sinusoidal endothelial cells (LSECs) in vivo in different stages of liver graft donation, in order to understand the effects of graft ischemia and perfusion on LSEC activity in liver grafts. Special attention was paid to grafts that underwent hypothermic oxygenated perfusion (HOPE). Forty-seven donors were prospectively enrolled, and two distinct biopsies were performed in each case: one allocation biopsy (at the stage of organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Based on the underlying mechanism of protection, this perfusion technique reduces posttransplant complications, improves graft survival and reduces re-transplantation rates [ 76 , 82 ]. The concept of improved peripheral sinusoidal flow and microvascular protection through the HOPE concept is also interesting [ 83 , 84 ]. In the context of LDLT, existing experimental studies demonstrated an improved growth and earlier entrance into the cell-cycle for quicker liver regeneration after hypothermic perfusion [ 85 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the underlying mechanism of protection, this perfusion technique reduces posttransplant complications, improves graft survival and reduces re-transplantation rates [ 76 , 82 ]. The concept of improved peripheral sinusoidal flow and microvascular protection through the HOPE concept is also interesting [ 83 , 84 ]. In the context of LDLT, existing experimental studies demonstrated an improved growth and earlier entrance into the cell-cycle for quicker liver regeneration after hypothermic perfusion [ 85 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Six studies used an animal model (either porcine or rodent), and one tested such effects in discarded human livers. Tissue samples from two clinical transplant studies were assessed for EC protection with HOPE and correlated with posttransplant outcomes [ 75 , 76 ]. One study combined rodent experiments with human liver transplants in a model of severe macrosteatosis [ 77 ].…”
Section: Effect Of Machine Perfusion On Mitochondria and Endothelial ...mentioning
confidence: 99%
“…Tissue samples from this study were assessed for EC integrity and activation. Vasuri et al analyzed 47 human livers from a randomized controlled trial (RCT) in Italy transplanting ECD livers with HOPE or cold storage [ 60 , 75 ]. The authors describe endothelial trophism and intracellular homeostasis measured through Nestin expression after HOPE.…”
Section: Effect Of Machine Perfusion On Mitochondria and Endothelial ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The second study provides a demonstration of the extracellular metabolism of nicotinamide adenine dinucleotide (NAD+) and nicotinamide mononucleotide (NMN), multifunctional metabolites involved in a number of cellular processes, and which is vastly different in its expression in the vascular endothelium obtained from different species and locations [2]. The third paper, instead, deals with the functions and intracellular mechanisms of endothelial cells in human liver grafts [3].…”
mentioning
confidence: 99%